2022
DOI: 10.1101/2022.04.29.490075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insights from short and long reads sequencing to explore cytochrome b variants of Plasmopara viticola populations collected in vineyard and related to resistance to complex III inhibitors

Abstract: Downy mildew is caused by Plasmopara viticola, an obligate oomycete plant pathogen, a devasting disease for grapevine. To preserve plants from the disease, complex III inhibitors are among the widely used fungicides that specifically target the mitochondrial cytochrome b (cytb) of the pathogen to block cellular respiration mechanisms. In French vineyard, P. viticola developed resistance against a first category of these fungicides, the Quinone outside inhibitors, by exhibiting a single amino acid substitution … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In both cases, the electron transfer process is blocked, leading to the inhibition of mitochondrial respiration [44][45][46]. Indeed, the quinone inside inhibitors used in agriculture are highly specific against oomycete pathogens [47,48]. Furthermore, it has previously been demonstrated that P.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the electron transfer process is blocked, leading to the inhibition of mitochondrial respiration [44][45][46]. Indeed, the quinone inside inhibitors used in agriculture are highly specific against oomycete pathogens [47,48]. Furthermore, it has previously been demonstrated that P.…”
Section: Discussionmentioning
confidence: 99%